Synthesis and Characterization of Coated CoFe2O4 Nanoparticles with Biocompatible Compounds and In Vitro Toxicity Assessment on Glioma Cell Lines - Ozer, Sevil; Dogan, Nurcan; Canim-Ates, Sezen; Bingolbali, Ayhan (WILEY-V C H VERLAG GMBH, 2025)
Rapid advances in the development of nanotechnology in recent years have led to functional magnetic nanoparticle types (MNPs) with different properties. The diverse applications of these nanoparticles make them a desirable candidate for use in biomedical areas due to their exclusive chemical and physical properties. The present work is conducted to study the in vitro biocompatibility of CoFe2O4@shell with different surface coatings (shell: ascorbic acid (AA), dextran (DEX), and polyethyleneimine (PEI). The cytotoxicity of coated nanoparticles is screened toward the glioma cancer line (C6) and fibroblast cell line (L929) using an MTT assay. CoFe2O4 NPs are synthesized using the co-precipitation method together with hydrothermal synthesis and characterized regarding their structural and magnetic properties using state-of-the-art techniques. Results showed the particles are consistent with the crystal structure of CoFe2O4 and the average crystallite size in the range of 16-18 nm. For the coated NPs, only a slight increase in the Hc is found except for the CoFe2O4@PEI NPs. The comparative analysis of the cytotoxic effects of CoFe2O4@shell NPs on L929 fibroblast and glioma cells shows that the cytotoxicity of samples is much more specific in brain tumor cells, especially it also indicates the significant efficacy of CoFe2O4@PEI in cancer cells.
Keywords: ascorbic acid (AA); biocompatibility; cobalt ferrite nanoparticles; co-precipitation method; dextran (DEX); glioma cell; hydrothermal synthesis; in vitro cytotoxicity; polyethyleneimine (PEI); IRON-OXIDE NANOPARTICLES; MAGNETIC-PROPERTIES; SUPERPARAMAGNETIC NANOPARTICLES; SURFACE FUNCTIONALIZATION; FE3O4 NANOPARTICLES; CANCER; SIZE; STABILITY; DEXTRAN; Chemistry; Materials Science